PENGARUH LABEL HALAL PADA KEMASAN INDOMIE GORENG TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - ABDULLAH, IMADUDDIN (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Requirement of food and beverage society will in tidiness mount either from facet of[is quality of and also amount in the last few years. By dozens from consumer pay attention lawful lable tidiness when will buy product in tidiness. Lawful lable found on tidiness of vital importance because from lable that's consumer know many matter concerning product they to consume. Producers have to assure consumer that their raw material is true fulfill standard to be consumed. One of them by raising lawful sertifikasi to LPPOM-MUI. Pursuant to mentioned, as for this research internal issue formula is do lawful lable have an effect on signifikan to decision of purchasing of Faculty Of Economics University Country student of Surabaya. Type Research use quantitative descriptive research. Analysis technique the used is Linear Regresi Modestly. Population the used is Faculty Of Economics University Country student of Surabaya. From result of research use analysis of regresi simple can be concluded that lawful lable can influence decision of purchasing equal to 0,728. Keywords: Lawful Lable and Decision of Purchasing.